Pengaruh Sukuk Bank Indonesia Dan Bi Rate Terhadap Inflasi di Indonesia Periode 2020-2023 - Rafil Pramana S.M. Arsad; Failur Rahman; Haerul Anam; Rita Yunus; Santi Yunus (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This study aims to determine the Effect of Company Growth and Operational Complexity on Auditor Switching Mediated by Audit Delay. The data used are secondary data taken from audited financial statements in 2021-2023. Sample selection was carried out using the purposive sampling method and the number of samples that met the criteria was 10 companies with 30 observations. This research method is a quantitative method. The hypothesis testing of this study uses logistic regression analysis and path analysis assisted by the Statistical Program for Special Science (SPSS) version 25. The results of this study indicate that partially company growth does not affect audit delay, operational complexity affects audit delay, company growth does not affect auditor switching, operational complexity affects auditor switching and audit delay does not affect auditor switching, Company growth through audit delay has an effect on auditor switching, and operational complexity through audit delay has an effect on auditor switching.